The Influence of Religion on Technological Advancement in Europe - Amilcar Alvonso (GoAcademica Research & Publishing, 2023)
Religion has played a significant role in shaping the development of technology in Europe, with its influence spanning historical epochs and contemporary debates. This article delves into the intricate interplay between faith and innovation, exploring how religious beliefs and institutions have both hindered and facilitated technological progress on the European continent. From the preservation of knowledge in monastic scriptoria to the ethical considerations surrounding biotechnology, this study uncovers the multifaceted relationship between religion and technology, offering insights into the complex dynamics that have defined Europe's technological journey. This examination serves as a reminder that understanding the role of religion in technological advancement is essential for comprehending the nuanced evolution of European society and its implications for the future.